2006
DOI: 10.1007/s10803-006-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Stories on Prosocial Behavior of Preschool Children with Autism Spectrum Disorders

Abstract: Social Stories are a popular intervention for preschool children with autism spectrum disorders (ASD), but little research on Social Stories has been conducted with this population. This study investigated the effects of Social Stories on prosocial behavior of three preschool children with ASD in an inclusive setting. An ABAB design was used for two participants, while an ABACBC was used for the third. Social Stories increased appropriate behavior and decreased inappropriate behavior for two participants. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
102
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 20 publications
(32 reference statements)
11
102
0
6
Order By: Relevance
“…Consequently, the opinions of both participants and teachers related to the study results were seen to be positive. This finding complies with the social validity findings obtained from other research conducted that had used the subjective evaluation approach on this subject (Akmanoğlu & Tekin-İftar, 2011;Croizer & Tincani, 2006;Delano, 2003;Dodd at al., 2008;Emecen, 2008;Graetz, 2003;Nikopoulos & Keenan, 2003;Sansosti & Powell-Smith, 2008;Scattone, 2008). However, data had only been collected from the teachers and families of participants in these studies using the subjective evaluation approach.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consequently, the opinions of both participants and teachers related to the study results were seen to be positive. This finding complies with the social validity findings obtained from other research conducted that had used the subjective evaluation approach on this subject (Akmanoğlu & Tekin-İftar, 2011;Croizer & Tincani, 2006;Delano, 2003;Dodd at al., 2008;Emecen, 2008;Graetz, 2003;Nikopoulos & Keenan, 2003;Sansosti & Powell-Smith, 2008;Scattone, 2008). However, data had only been collected from the teachers and families of participants in these studies using the subjective evaluation approach.…”
Section: Discussionsupporting
confidence: 91%
“…Maintenance data revealed that the target social skills acquired by the participants had been maintained after completion of the intervention. Maintenance data collected from many studies that examined the effectiveness of interventions using video modeling, Social Stories, or the combination of the two showed that participants had maintained the acquired skills after the intervention terminated (Akmanoğlu & Tekin-İftar 2011;Bidwell & Rehfeldt, 2004;Croizer & Tincani, 2006;Delano, 2003;Delano & Snell, 2006;Gena et al, 2005;Graetz, 2003;Keyworth, 2004;Kuoch & Mirenda, 2003;Nikopoulos & Keenan, 2003;Özdemir, 2008;Quilty, 2007;Reichow & Sabornie, 2009;Sansosti & Powell-Smith, 2008;Schenider & Goldstein, 2010;Swaine, 2004;Washburn, 2006;Wert & Neisworth, 2003;Xin & Sutman, 2011). The maintenance findings of this study were similar to findings from other research; this supports the findings in the literature.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The stories help the child with ASD understand how someone else might be feeling, and how they can respond appropriately [7,8]. Literature shows that the stories improve the child with ASD's understanding of social expectations for behavior in multiple studies across a variety of settings [9][10][11][12][13]. Both these methods are thought to improve the child's expectations of routines and behaviors expected of them during the routines.…”
Section: Introductionmentioning
confidence: 99%